2009
DOI: 10.1016/j.nbd.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 inhibitors show benefits in an Alzheimer's disease (AD) model of neurodegeneration but adverse effects in control animals

Abstract: The dysregulation of glycogen synthase kinase-3 (GSK3) has been implicated in Alzheimer disease (AD) pathogenesis and in Aβ-induced neurotoxicity, leading us to investigate it as a therapeutic target in an intracerebroventricular Aβ infusion model. Infusion of a specific GSK3 inhibitor SB216763 (SB) reduced a downstream target, phospho-glycogen synthase 39%, and increased glycogen levels 44%, suggesting effective inhibition of enzyme activity. Compared to vehicle, Aβ increased GSK3 activity, and was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 78 publications
5
93
1
1
Order By: Relevance
“…Overexpression of GSK-3 induces cell death and its inhibition is protective (Miura and Miki 2009). As several studies have shown that administration of a GSK-3b inhibitor can protect cultured neurons against excitotoxicity and toxin-induced apoptosis (Liang and Chuang 2007;Chuang et al 2011), and reduce the presence of pyknotic neurons in a model of Alzheimer's disease (Hu et al 2009), we questioned if similar benefits could be observed following stroke by using the potent and selective GSK-3b Figure 2. Neuroprotection was seen with delayed treatment with a GSK-3b inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GSK-3 induces cell death and its inhibition is protective (Miura and Miki 2009). As several studies have shown that administration of a GSK-3b inhibitor can protect cultured neurons against excitotoxicity and toxin-induced apoptosis (Liang and Chuang 2007;Chuang et al 2011), and reduce the presence of pyknotic neurons in a model of Alzheimer's disease (Hu et al 2009), we questioned if similar benefits could be observed following stroke by using the potent and selective GSK-3b Figure 2. Neuroprotection was seen with delayed treatment with a GSK-3b inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, it is neither a potent nor specific inhibitor of GSK-3. 94 In fact, neuronal deficits have been reported to result from both genetic reduction and specific inhibition of GSK-3, 95,96 highlighting the risk of inhibiting this enzyme. 97 Lithium arrests neuropathology in some AD rodent models, 36,38,39 but these are aggressive models driven by transgene overexpression, where the benefits of lithium inhibiting a dominant pathological target (for example, tau hyperphosphorylation) outweigh lithium-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral tissues, both JNK and ERK phosphorylate IRS-1 at Ser307 (rodent equivalent for human Ser312) (Aguirre et al, 2000) and Ser616 (D'Alessandris et al, 2007). The resulting loss of IRS-1 coupling to PI3-K/Akt is predicted to activate another major tau kinase, GSK3␤, which is known to be activated by A␤ (Takashima et al, 1996;Ma et al, 2006;Hu et al, 2009). This process further dysregulates insulin signaling since GSK3 itself directly phosphorylates IRS-1 at Ser332 to help inactivate IRS-1 (Liberman and Eldar-Finkelman, 2005).…”
Section: Discussionmentioning
confidence: 99%